Early-Life Risk Factors and Clinical Features of Food Allergy Among Thai Children - Samkhwan Thongsukkaeo; Yiwa Suksawat (International Journal of Pediatrics)
Conclusions: In this study, risk factors associated with food allergy comprised a personal history of atopic dermatitis and a family allergic disease, which may be used as predictive factors for developing food allergy among Thai children.